Cash Waqf Linked Deposit Potential for Revitalizing Islamic Banking in Indonesia - Utomo, Gunawan Setyo; Ismal, Rifki (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
Despite existing for over two decades, the market share of Islamic banking remains stagnant. Conversely, Indonesia possesses immense, yet underutilized, potential for cash waqf (charitable endowments). This study investigates the Cash Waqf Linked Deposit (CWLD) product, an initiative by OJK, focusing on its potential to enhance Islamic bank participation in cash waqf management. The research explores the responses of cash waqf participants through in-depth interviews and Focus Group Discussions (FGDs) with seven key figures: two waqif (donors), three representatives from LKS PWU (waqf collecting institutions), and two nazir (managers). Descriptive qualitative analysis facilitated by NVivo software is employed to understand the responses. The findings reveal a high level of alignment (70% average word similarity) between the proposed CWLD product design and stakeholder expectations. All stakeholders expressed positive responses and support for CWLD. They perceive CWLD as a facilitator for waqf contributions through Islamic banks, a means to expand existing waqf assets, and an attractive option due to the temporary nature of the deposits with eventual return to the waqf. This study highlights the potential of CWLD to bridge the gap between Islamic banking and cash waqf in Indonesia, potentially contributing to a more dynamic Islamic banking landscape.==============================================================================================================ABSTRAK – Potensi Cash Waqf Linked Deposit dalam Revitalisasi Perbankan Syariah di Indonesia. Pangsa pasar perbankan syariah menunjukkan stagnasi meskipun sudah beroperasi selama lebih dari dua dekade. Di sisi lain, potensi wakaf uang di Indonesia sangat besar, namun belum difasilitasi secara optimal oleh perbankan syariah. Penelitian ini bertujuan untuk mengevaluasi produk Cash Waqf Linked Deposit (CWLD) yang diinisiasi oleh OJK, dengan fokus pada respons para pemangku kepentingan wakaf uang. Data penelitian dikumpulkan melalui wawancara mendalam dan Focus Group Discussion (FGD) dengan tujuh narasumber kunci, yaitu dua waqif (pemberi wakaf), tiga perwakilan LKS PWU (lembaga pengumpul wakaf uang), dan dua nazir (pengelola wakaf). Untuk memahami tanggapan responden, penelitian ini menggunakan analisis kualitatif deskriptif dengan bantuan perangkat lunak NVivo. Hasil penelitian menunjukkan bahwa desain dan usulan produk CWLD yang diinisiasi oleh OJK telah sangat mengakomodasi aspirasi dan harapan para pemangku kepentingan. Analisis kesamaan kata antar wawancara menunjukkan rata-rata 70%, yang mengindikasikan kesesuaian produk dengan kebutuhan pemangku kepentingan. Para pemangku kepentingan memberikan respons positif dan dukungan terhadap usulan produk CWLD. Mereka memandang CWLD sebagai fasilitator bagi waqif untuk melakukan wakaf melalui bank syariah, produk alternatif untuk meningkatkan aset wakaf yang sudah ada, dan pilihan menarik bagi waqif karena dana wakaf bersifat sementara dan akan kembali kepada waqif. Hasil kajian ini menggarisbawahi besarnya potensi CWLD dalam menjawab persoalan stagnasi pangsa pasar perbankan syariah dengan memanfaatkan potensi wakaf uang yang besar di Indonesia.